2D/1D MoS2/TiO2 Heterostructure Photocatalyst with a Switchable CO2 Reduction Product. Issue 1 (21st November 2022) - Hezam, Abdo; Alkanad, Khaled; Bajiri, Mohammed Abdullah; Strunk, Jennifer; Takahashi, Keisuke; Drmosh, Qasem Ahmed; Al‐Zaqri, Nabil; Krishnappagowda, Lokanath Neratur
Abstract: Regulating the transfer pathway of charge carriers in heterostructure photocatalysts is of great importance for selective CO2 photoreduction. Herein, the charge transfer pathway and in turn the redox potential succeeded to regulate in 2D MoS2 /1D TiO2 heterostructure by varying the light wavelength range. Several in situ measurements and experiments confirm that charge transfer follows either an S‐scheme mechanism under simulated solar irradiation or a heterojunction approach under visible light illumination, elucidating the switchable property of the MoS2 /TiO2 heterostructure. Replacing the simulated sunlight irradiation with the visible light illumination switches the photocatalytic CO2 reduction product from CO to CH4. 13 CO2 isotope labeling confirms that CO2 is the source of carbon for CH4 and CO products. The photoelectrochemical H2 generation further supports the switching property of MoS2 /TiO2 . Unlike previous studies, density functional theory calculations are used to investigate the band structure of Van der Waals MoS2 /TiO2 S scheme after contact, allowing to propose accurate charge transfer pathways, in which the theoretical results are well matched with the experimental results. This work opens the opportunity to develop photocatalysts with switchable charge transport and tunable redox potential for selective artificial photosynthesis. Abstract : Replacing the simulated sunlight irradiation with the visible light illumination switches the charge transfer in 2D/1D MoS2 /TiO2 heterostructure from the S‐scheme mechanism to the heterojunction mechanism and in turn changes the CO2 photoreduction product from CO to CH4 .